Guest

IF atanA+btanB=(a+b)tan((A+B)/2), a not equal to 0. then prove that:acosB=bcosA.

IF atanA+btanB=(a+b)tan((A+B)/2), a not equal to 0. then prove that:acosB=bcosA.

Grade:11

1 Answers

mycroft holmes
272 Points
11 years ago

Hence, the equation can be written as 

After cross multiplying and simplifying, we get 

or 

If sin(A-B) \= 0, then a cos B = b cos A

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free